Arabic Language Learning in a Multicultural Context at Pesantren - Asep Sopian; Maman Abdurahman; Mad 'Ali; Yusuf Ali Tantowi; Ani Nur Aeni; Hikmah Maulani (Jurnal Pendidikan Islam)
Arabic language education in Indonesia faces the challenge of being perceived as mono-cultural and narrowly religious, often excluding broader multicultural contexts. This study explores Arabic language learning in pesantren (Islamic boarding schools) across culturally diverse regions in Indonesia to identify how multicultural values are integrated into the curriculum. Employing a qualitative phenomenological approach, the research was conducted in six provinces: West Java, Central Java, East Java, Lombok, Bali, and Sulawesi. Data were collected through in-depth interviews and surveys involving 50 Arabic teachers and 300 students in pesantren institutions. The findings reveal that Arabic learning in pesantren reflects four key dimensions of multicultural integration: cultural, social, intellectual, and spiritual. These dimensions shape learners’ engagement with Arabic not only as a religious language but also as a medium for intercultural dialogue and identity negotiation. Additionally, regional cultural influences significantly affect teaching strategies and learners’ motivations. The research highlights the potential of pesantren to serve as transformative spaces for multicultural Islamic education, bridging religious values with local cultural diversity. This study underscores the importance of recontextualizing Arabic instruction within Indonesia’s multicultural society, promoting inclusivity while maintaining pesantren’s core religious missions in the evolving landscape of education in the era of the Industrial Revolution 4.0.